(In)visible urban water networks: the politics of non-payment in Manila's low-income communities. (April 2013) - Cheng, Deborah
The oft-purported goals of good urban water governance include universal coverage and low levels of water loss. However, such goals can be particularly challenging in large, metropolitan areas where infrastructure may be ageing or unknown. This paper clarifies the mechanisms through which urban infrastructure is made visible – and thus more governable – by examining the politics of non-payment in Manila and the techniques that the two private concessionaires use to reclaim lost revenues. While some customers from all income levels may evade payment, the mechanisms for payment recovery targeted at low-income consumers focus on increased policing and a transfer of responsibility towards communities and individuals and away from the concessionaires. In contrast, payment recovery targeted at high volume customers typically involves technical improvements and settlement of arrears. The differentiated treatment of the poor and non-poor thus has four failures: first, while visibility is directed at payment recovery, those that are unserved or underserved remain invisible through the propagation of aggregate statistics characterizing greater coverage and reductions in system losses; second, there is an asymmetry of treatment for non-payment in poor and non-poor areas, which can result in higher costs in poorer areas; third, the same processes that lead to greater coverage and reduced losses also reconfigure inequalities; and fourth, small water providers are increasingly becoming the policing arm of the utilities rather than competitive alternatives. Recognizing remaining inequalities in cities like Manila helps to highlight the situation for the underserved and allows us to re-imagine ways of achieving universal access.